2003
DOI: 10.1136/oem.60.5.348
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer and serum organochlorine residues

Abstract: Background: Controversy still exists about the breast carcinogenic properties in humans of environmental xenoestrogens (organochlorines), justifying new investigations. Aims: To compare the blood levels of total dichlorodiphenyltrichloroethane (DDT) and hexachlorobenzene (HCB) in samples collected at the time of breast cancer discovery, in order to avoid the potential consequences of body weight change (after chemotherapy or radiotherapy) on the pesticide residue levels. Methods: Blood levels of HCB and total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(43 citation statements)
references
References 28 publications
(13 reference statements)
1
39
0
3
Order By: Relevance
“…We did not find consistent dose-response trends or consistency within categories of exposure, including the chemical type (persistent, residue from persistent, or less persistent), method of application (aerial or ground), and type of use (e.g., cranberry cultivation, tree pest control). These findings are consistent with results of many recent studies of certain organochlorine pesticides and breast cancer (Gammon et al 2002, Laden et al 2001Snedeker 2001), although associations have been reported in some others (Charlier et al 2003;Cohn et al 2002;Hoyer et al 1998Hoyer et al , 2000Hoyer et al , 2002. The present study adds to this literature by using novel GIS-based methods that assess exposures to mixtures of many chemicals from multiple types of use over many years.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We did not find consistent dose-response trends or consistency within categories of exposure, including the chemical type (persistent, residue from persistent, or less persistent), method of application (aerial or ground), and type of use (e.g., cranberry cultivation, tree pest control). These findings are consistent with results of many recent studies of certain organochlorine pesticides and breast cancer (Gammon et al 2002, Laden et al 2001Snedeker 2001), although associations have been reported in some others (Charlier et al 2003;Cohn et al 2002;Hoyer et al 1998Hoyer et al , 2000Hoyer et al , 2002. The present study adds to this literature by using novel GIS-based methods that assess exposures to mixtures of many chemicals from multiple types of use over many years.…”
Section: Discussionsupporting
confidence: 92%
“…Previous investigations include a small number of occupational and ecologic studies, with both positive and null findings (Abdalla et al 2003;Band et al 2000;Dolapsakis et al 2001;Fleming et al 1999aFleming et al , 1999bHopenhayn-Rich et al 2002;Janssens et al 2001;Kettles et al 1997;Kogevinas et al 1993;Manz et al 1991), and a larger number of population-based studies of serum and adipose measurements of dichlorodiphenyltrichloroethane (DDT), its metabolite dichlorodiphenyldichloroethene (DDE), and a few other persistent organochlorines [reviewed by Brody and Rudel (2003)]. Many of the serum studies failed to find an association with breast cancer (Gammon et al 2002;Laden et al 2001;Snedeker 2001); however, a few have shown positive associations (Charlier et al 2003;Cohn et al 2002;Hoyer et al 1998Hoyer et al , 2000Hoyer et al , 2002.…”
mentioning
confidence: 99%
“…Of the remaining 8 studies, the results were mixed. While 4 studies 163,165,169,170 did not observe an association between OC concentrations, the other 4 studies 164,166,168,171 did observe positive associations.…”
Section: Nonoccupational Oc Insecticide Exposure and Breast Cancermentioning
confidence: 91%
“…In our current review, we update the literature since 2002. We identified 11 published studies 32,[162][163][164][165][166][167][168][169][170][171] that reported on associations between measured serum, plasma, or adipose tissue concentrations of OC insecticides and breast cancer, which were not included in either the review by Calle et al or Lopez-Cervantes et al 160,161 Two studies 162,167 were excluded from our review because risk estimates (eg, ORs) were not reported. A third study 32 was excluded because the case definition included prevalent breast cancer.…”
Section: Nonoccupational Oc Insecticide Exposure and Breast Cancermentioning
confidence: 99%
“…However, there have been conflicting reports on the relationship between exposure to low levels of POPs, such as those occurring in the general population, and cancer risk, with some studies reporting positive associations but many others finding no evidence to support a causal association (Cassidy et al, 2005;Charlier et al, 2003;Cohn et al, 2010;Gatto et al, 2007;Govett et al, 2011;Hardell et al, 2006;Hoyer et al, 2001;Laden et al, 2001;Lopez-Carrillo et al, 2002;Lopez-Cervantes et al, 2004;Mozzachio et al, 2008;Pavuk et al, 2004;Recio-Vega et al, 2011;Snedeker, 2001;Soto and Sonnenschein, 2010;Svensson et al, 1995;Ward et al, 2000;Wolff et al, 2000;Xu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%